KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK SAGU DENGAN SUBTITUSI TAPIOKA DAN BUBUR RUMPUT LAUT (Eucheuma cottonii) - Lestari, Endang; Maherawati, Maherawati; Rahayuni, Tri (Jurnal Gizi dan Pangan Soedirman, 2023)
Sago is a source of carbohydrates that has the potential to be used as a raw material for processed foods such as crackers. Crackers are a food that people like because they crunchy and can be used as a snack or complementary to the main daily menu. Improving the quality of sago crackers can be done by subtituting tapioca and seaweed pulp, which will provide more swelling power and higher protein levels. This research aims to determine the effect of subtituting tapioca and seaweed slurry on the physicochemical and organoleptic characteristics of sago crackers and determine the formulation that produces the best sago crackers. The design used was a Randomized Block Design (RBD) with one factor (p) ,consisting of 6 treatment levels and four replications. The results showed that subtituting tapioca and seaweed porridge affected the swelling power, water content, ash content, and protein content of sago crackers but did not affect the fat and carbohydrate content. The subtitution of tapioca and seaweed slurry produced the best physicochemical and organoleptic properties in the formulation of sago starch: tapioca: seaweed slurry (70:5:25) with swelling power of 76.78%, water content of 7.06%, ash content of 2.86%, fat content 12.88%, protein content 0.56%, carbohydrate content 77.72%, color 3.47 (like-very like), aroma 2.97 (dislike-like), taste 3.57 (like -like very much), crispness 3.73 (like-very like) and overall likeability 3.67 (like-very like).